Characterization of pH-fractionated humic acids with respect to their dissociation behaviour - Klučáková, Martina (Environmental science and pollution research international, 2016)
Humic acids were divided into several fractions using buffer solutions as extraction agents with different pH values. Two methods of fractionation were used. The first one was subsequent dissolution of bulk humic acids in buffers adjusted to different pH. The second one was sequential dissolution in buffers with increasing pH values. Experimental data were compared with hypothesis of partial solubility of humic acids in aqueous solutions. Behaviour of humic fractions obtained by sequential dissolution, original bulk sample and residual fractions obtained by subsequent dissolution at pH 10 and 12 agrees with the hypothesis. Results demonstrated that regardless the common mechanism, solubility and dissociation degree of various humic fractions may be very different and can be estimated using parameters of the model based on the proposed mechanism. Presented results suggest that dissolving of solid humic acids in water environment is more complex than conventional solubility behaviour of sparingly soluble solids.
Keywords: Acid–base behaviour; Polyelectrolyte; Buffers; Humic Substances; Hydrogen-Ion Concentration; chemické modely; koncentrace vodíkových iontů; huminové látky; Humic acid; chemická frakcionace; pufry; rozpustnost; Chemical Fractionation; Models, Chemical; Dissociation; Fractionation; Solubility